The Significance of the Region for Urban Growth: The Example of Bonn and the Rhein-Sieg District. - Tengler, Hermann (Springer, 2018)
Urban growth is driven by structural change in the economy. While the manufacturing sector is moving away from the cities, the fast-growing company-oriented and knowledge-based services are drawn into the urban centers. There they find the most favorable conditions, allowing them to develop in an above average way.The suburban area is becoming increasingly significant to urban growth. In addition to its traditional relief function regarding residential and business areas, it is the spatial division of labor that emerged in the sectoral structural change, which supports urban growth. The highly competitive industry located in the suburban area represents the most important consumer of services concentrated in the cities. To stand its ground within the global competition of innovation, industry must be able to revert to application-oriented knowledge. For this purpose, an increasing number of training, research and technology transfer services were established outside of the major cities over the last few years. They are tailored to the specific needs of the regional economy and benefit the development of the entire region.The City of Bonn and the Rhein-Sieg District can serve as a model for the cross-pollination of the city and its surrounding area. After losing its status as Germany s governmental seat, the region has so far successfully mastered the structural change through cooperation. At the same time, the first signs indicating a gradual shift of the growth from the city towards the region can be detected from the development of the two local authorities as well as the recent migration movement in the large cities.
Keywords: Regionalwirtschaft; Stadtökonomie; Strukturwandel; Reurbanisierung